Molecular characterization of rhizobacteria isolated from walnut (Juglans regia) rhizosphere in Western Himalayas and assessment of their plant growth promoting activities - GH. HASSAN DAR; SHAKEELA SOFI; S.A. PADDER; AISHA KABLI (Society for Indonesian Biodiversity, 2018)
Dar GH, Sofi S, Padder SA, Aisha Kabli A. 2018. Molecular characterization of rhizobacteria isolated from walnut (Juglans regia) rhizosphere in Western Himalayas and assessment of their plant growth promoting activities. Biodiversitas 19: 712-719. The present study was aimed to isolate and characterize effective bacteria from the rhizosphere of walnut (Juglans regia) grown in North Western Himalayas and assess their growth promoting potential so that they may, in future, be exploited as biofertilizers. Based on preliminary screening of 98 bacterial isolates obtained from four walnut growing districts of Kashmir valley during survey in 2015, 12 isolates were characterized morpho-biochemically and molecularly basis. On the basis of 16S rDNA sequencing they were identified as Bacillus licheniformis WI 90, B. tequilensis WI 62, B. cereus WI 36, B. subtilis strains WI 63 and WI 65, Micrococcus luteus strains WI 12, WI 41 and WI 80; M. yunnanensis strains WI 60 and WI 30 and Micrococcus sp. strains WI 11 and WI 91. The assessment of these rhizobacteria for plant growth promoting attributes revealed that B. licheniformis WI 90 possessed higher phosphorus solubilization activity (312 mg/L), followed by Micrococcus sp. WI 91 (267 mg/L) while high siderophore was produced by M. luteus WI 12 (27.2% siderophore units), followed by B. licheniformis WI 90. B. cereus strains WI 36. High IAA contents (30 µg/mL) was yielded by WI 41, followed by M. yunnanensis WI 60 (28 µg IAA/mL) while higher and statistically at par gibberellic acid was produced by B. licheniformis WI 90, Micrococcus sp. WI 91 and M. luteus WI 80. Higher chitinase enzyme activity was observed in B. subtilis WI 63 (30.5 units/mL), followed by B. tequilensis WI 62 (25.3 units/mL) and B. subtilis WI 65 (25.1 units/mL). The study revealed high plant growth promoting potential in these rhizobacteria.